Ebola and Marburg viruses IgG detections in small ruminants and dogs from villages within outbreak areas in Gabon. - Telstar G Ndong Mebaley; Pierre Becquart; Matthieu Fritz; Eric Elguero; Illich M Mombo; Déborah C Garcia; Linda Bohou Kombila; Léadisaelle H Lenguiya; Larson Boundenga; Eric M Leroy; Gael D Maganga (PLoS ONE)
The Ebola virus (EBOV) and Marburg virus (MARV) have been in circulation in Africa for several decades and are the cause of numerous outbreaks. There has been very little research on the role of domestic animals in their transmission to humans, but studies have only been conducted in dogs and pigs where relatively high levels of IgG was detected. These levels suggest that ruminants, which have not been studied, should also be investigated. This study aims at evaluating the circulation of MARV and EBOV in dogs, sheep and goats and to assess their exposure to these two viruses. Between November 2018 and March 2023, a total of 448 domestic animal sera or plasma samples, including 128 dogs, 222 goats and 98 sheep, were analyzed by serological and molecular methods. The Luminex technique was employed for the detection of IgG antibodies against EBOV NP, GP, MARV GP and VP40, while EBOV specific and pan-filovirus polymerase chain reaction amplification was used for molecular analysis. All samples tested negative for EBOV and MARV RNA. However, our results showed that 2/128 (1.5%) dogs, 1/222 (0.4%) goats and 3/98 (3.1%) sheep displayed NP and GP anti-EBOV antibodies. In addition, 2/128 (1.5%) dogs displayed GP and VP40 anti-MARV antibodies, while no antibodies were detected in goats and sheep. Over all, these results suggest that dogs and small ruminants are naturally exposed to EBOV and MARV. In the absence of clinically sick individuals, the presence of IgG-positive animals suggests various sources of exposure, such as contaminated fruits with the urine and saliva of bats or dead bats fallen on the ground ate by dogs. These contaminated substrates are both consumed by both dogs and small ruminants. The findings provide new insights into the circulation and exposure of EBOV and MARV in domestic animals, emphasising their potential use as sentinels. Furthermore, they prompt significant considerations regarding the potential risk to humans in this region.